Biological–physical oceanographic coupling influencing particulate organic matter in the South Yellow Sea - Guo, Congcong; Yang, Shu; Zhai, Weidong; Niu, Yao; Liu, Chunli (Frontiers in Marine Science, 2022)
Using total suspended matter (TSM), particulate organic carbon (POC), and particulate nitrogen data, this study investigated the potential vertical POC flux and transport in the South Yellow Sea (SYS). The biogenic production and resuspension fraction (i.e., the proportion of resuspended particles in TSM) were estimated using an ecosystem model and a vertical mixing model. They were verified against reported sediment trap and primary productivity data. The estimates of resuspension fraction showed substantial uncertainty of 50% in summer likely owing to the potential errors of model parameter estimation and the influence of other unexplored biophysical processes such as biological degradation, upwelling, and monsoons; however, the estimates of resuspension fraction showed less uncertainty in other seasons (<20%). Few previous studies have considered the specific influence of resuspension on the dynamics and budget of particulate organic matter (POM) in the SYS. This study proposed a reasonably simple and effective method to address this issue, which was applied to systematic examination of the variation of vertical POM flux with the change of coupled biological–physical oceanographic processes along the Subei coast and in the SYS central basin. The influence of horizontal transport from the Subei coast to the central basin may cause an overestimation of >10% of the resuspension fraction. It will be necessary to acquire additional field data covering a larger spatiotemporal scale to establish an integrated network of the SYS carbon budget.